On AI-Inspired User Interface Design - Wei, Jialiang; Courbis, Anne-Lise; Lambolais, Thomas; Dray, Gerard; Maalej, Walid (IEEE software, 2025)
A graphical user interface is a primary means of interaction between users and their devices. Here we discuss three complementary AI approaches for triggering the creativity of app designers and inspiring them create better, more diverse user interface designs.